Technology, Communication, and the Performance of financial Markets: 1840-1975: Discussion - Edwards, Franklin R. (Journal of Finance, 1978)
Franklin R. Edwards, Technology, Communication, and the Performance of financial Markets: 1840-1975: Discussion, The Journal of Finance, Vol. 33, No. 3, Papers and Proceedings of the Thirty-Sixth Annual Meeting American Finance Association, New York City December 28-30, 1977 (Jun., 1978), pp. 845-847